جماليات الفن الإسلامي وأهميتها في الدعوة إلى الله سبحانه وتعالى: دراسة تحليلية : The Aesthetics of Islamic Art and its Importance in Calling to Allah: An analytical study - alashari, duaa (‘Abqari Journal, 2022)
This research aims to introduce Islamic art and its active role in calling to God Almighty by revealing the aesthetic views of Islamic art in Islamic thought and the importance of Islamic art with its various patterns in calling to God. This research also aims to identify the cognitive concepts of the aesthetics of Islamic art through the Islamic perspective. One of the most important questions posed by the research revolves around the aesthetic cognitive concepts of Islamic art through the Islamic perspective? And Also, about the aesthetic views and principles of Islamic art in Islamic thought and its role in calling to God? The method used in this study is the content analysis method, as it is the most appropriate type of curriculum in terms of the current research directions and objectives. The study reached a number of results, including Islamic art has its own concept, attributed to Islam and linked to the Islamic faith. The study also concluded that Islamic art is an integrated structural system with its concepts and principles that distinguish it from other arts, and make it an original art with advocacy values ​​that bring the slave closer to his Lord through the endless patterns that are embodied within Islamic art. يهدف هذا البحث إلى التعريف بالفن الإسلامي ودوره الفاعل في الدعوة إلى الله سبحانه وتعالى من خلال الكشف عن الآراء الجمالية للفن الإسلامي في الفكر الإسلامي وأهمية الفن الإسلامي بأنماطه المتنوعة في الدعوة إلى الله. كما يهدف هذا البحث إلى التعرف على المفاهيم المعرفية والخصائص الجمالية للفن الإسلامي من خلال المنظور الإسلامي. ومن أهم الأسئلة التي يطرحها البحث تتمحور حول المفاهيم المعرفية والجمالية للفن الإسلامي من خلال المنظور الإسلامي؟ وأيضاً حول الآراء والمبادئ الجمالية للفن الإسلامي في الفكر الإسلامي ودورها في الدعوة إلى الله؟ المنهج المتبع في هذه الدراسة هو منهج تحليل المحتوى كونه انسب أنواع المناهج من حيث توجهات وأهداف البحث الحالي. وتوصلت الدراسة إلى عدد من النتائج كان من بينها: هو أن الفن الإسلامي له مفهومه الخاص به، المنسوب إلى الإسلام والمرتبط بعقيدة الدين الإسلامي. كما توصلت الدراسة إلى أن الفن الإسلامي نسقًا بنائيًا متكامل له مفاهيمه ومبادئه التي تميزه عن غيره من الفنون، وتجعل منه فن أصيل ذو قيم دعوية تقرب العبد المسلم من ربه من خلال الأنساق اللامتناهية التي تتجسد ضمن الفن الإسلامي.